Genome-wide association studies in schizophrenia, and potential etiological and functional implications of their results - Hosák, Ladislav; Šilhán, Petr; Hosáková, Jiřina (Acta Medica, 2012)
Background: Despite the fact that the genetic basis of schizophrenia has been intensively studied for more than two decades, our contemporary knowledge in this field is rather fractional, and a substantial part of it is still missing. The aim of this review article is to sum up the data coming from genome‑wide association genetic studies in schizophrenia, and indicate prospective directions of further scientific endeavour. Methods: We searched the National Human Genome Research Institute’s Catalog of genome‑wide association studies for schizophrenia to identify all papers related to this topic. In consequence, we looked up the possible relevancy of these findings for etiology and pathogenesis of schizophrenia using the computer gene and PubMed databases. Results: Eighteen genome‑wide association studies in schizophrenia have been published till now, referring to fifty‑seven genes supposedly involved into schizophrenia’s etiopathogenesis. Most of these genes are related to neurodevelopment, neuroendocrinology, and immunology. Conclusions: It is reasonable to predict that complex studies of sufficiently large samples, involving detection of copy number variants and assessment of endophenotypes, will produce definitive discoveries of genetic risk factors for schizophrenia in the future.
Keywords: lidé; Genome-Wide Association Study; Schizophrenia; celogenomová asociační studie; schizofrenie; Humans